PROGRAM OPTIMALISASI SINERGITAS BUMDES DAN UMKM DI DESA TEGAL HARUM DENPASAR BARAT PASCA PANDEMI COVID-19 - Ida ayu putu Widani Sugianingrat; Putu Yudy Wijaya; Anak Agung Ngurah Gede Sadiartha; I Made Astrama (Universitas Hindu Indonesia, 2023)
The development of BUMDes and MSMEs is very important to do after previously Bali experienced an economic downturn due to the Covid-19 Pandemic. MSMEs are the main driving force for the rise of the Balinese economy because MSMEs are the sector that absorbs the most labor and is able to increase the value of consumption in society. This community service is focused and focuses on optimizing the performance of BumDes and MSMEs in post-Covid economic recovery and providing marketing methods that are in line with BUMDes and MSMEs with the latest developments in digital technology. This activity was attended by 30 participants consisting of village government structuralists, BUMDes, and MSMEs in Tegal Harum Village, West Denpasar and was carried out using mentoring, training and discussion methods. Participation of participants in this service activity was very enthusiastic and proactive. The results of community service activities in general include several components, namely: 1) The success of the target number of training participants; 2) Achievement of training objectives; 3) Achievement of planned training material targets; 4) The ability of participants to understand the training material